Digitalno oblikovanje in tisk - Šterman, Sonja; Neral, Branko (University of Maribor Press, 2018)
Digital Design and Printing. The textbook provides basic knowledge of digital design techniques, textile printing and imprint quality evaluation. The first chapter includes the field of design and digital design of textile patterns using various software tools in the media. The computer approach to design is presented in Chapter 2 with graphic system units, such as a scanner, a digital camera, a display, a plotter, a cutter, and a printer. The third chapter gives the basics of computer graphics in its use, and the differences between the vector and the bit principle. The fourth part presents color models in color spaces and their basic characteristics. Chapter 5 includes color management that combines software and measurement equipment and procedures that ensure the portability and repeatability of colors between different input-output units and between the computer graphic system software tools. The sixth chapter presents the basic building blocks of printing: reporting of the textile patterns, preparation of textiles, properties of hostels, colors and printing aids (auxiliary means). Basic methods, techniques and procedures of printing textiles depending on the raw material composition of the textile material are also given. Chapter Seven is familiar with the phases and purpose of textile processing after printing: from drying and curing (hardening), to washing of prints. The basic parameters for assessing the quality of printed textiles are described in Chapter 8.